High technology trade, absorptive capabilities and economic growth in Malaysia - Lam, Fong Litt Leonard (2019)
For the past several decades, Malaysia has witnessed strong economic growth and has become one of the Asian newly industrialised countries. Although Malaysian Gross National Income per capita has steadily increasing throughout the years, nevertheless, the performance of economic growth is quite dismal – categorising Malaysia under middle income trap. Malaysia is in need of a breakthrough in income per capita and economic growth in order to leap out of middle income trap and to achieve high income nation target. High technology manufacturing and high technology trade have been growing fast in world trade and it is likely to project significant impact to economic growth. Therefore, the general objective of this study is to explore the role played by high technology trade in transforming the Malaysian economy. The study is conducted using ARDL and FMOLS (as robustness checking) on quarterly data from 1990 to 2015. The involvement in high technology trade creates query on the factors that built a successful high technology trade especially in the case of transition economy like Malaysia. Thus, the first objective of the study is to explore the potential factors or determinants of high technology trade. Upon examination of the direct effect from the determinants of high technology trade, the study is also interested in the examination of the indirect effect of high technology trade to economic growth. As projection in GDP growth since the 1990s do not exhibit breakthrough, the study wonders upon the validation of missing absorptive capabilities that enhance high impact growth to the economy. Findings from the study successfully answered the first objective of the study. There is an indirect effect from absorptive capabilities as trade openness has significant impact when it interacts with research and development and foreign direct investment. Apart from research and development and foreign direct investment, the study also concludes direct effect that positively influences high technology trade from presence of infrastructure and financial development. The study also intends to extend into disaggregate level by recognising the niche area for specific subsectors of high technology industry that are worth of resource allocation and policy implications. Five largest trading Malaysian sectors of high technology industry are chosen for the study, namely (1) Machinery and Transport Equipment, (2) Mineral Fuels, Lubricants, etc., (3) Manufactured Goods, (4) Chemicals, and, (5) Miscellaneous Manufactured Articles. Taking into account of trade openness as absorptive capabilities, the study discovers Chemicals has the most promising result under model (RD x TO), while Machinery and Transport Equipment has the most promising result under model (FDI x TO). As the nature of high technology industry carries heavy weightage into research and development, being innovative is said to be one important score to sustainable growth. Only when a nation experiences sustainable growth, it has the ability to generate high impact growth to leap out of the middle income trap. This study is motivated by the view that high technology industry and its subsectors have the ability to generate high income for Malaysia to become a developed nation. Hence, the third objective of the study is to analyse the role that innovation plays in mediating the influence of high technology trade (selected subsectors) on economic growth. Empirical results on both aggregate and disaggregate level summarise that interaction between innovation with Chemicals sector has significant impact to economic growth in short run and long run – proving the existence of a high impact growth for the country to leap out of the middle income trap. Channelling the appropriate attention to policies that are developing the Chemicals sector and building up innovation culture in this sector is crucial. he abstract is a digest of the entire thesis and should be given the same consideration as the main text. It does not normally include any reference to the literature. Abbreviations or acronyms must be preceded by the full term at the first use. An abstract should be between 300-500 words. It includes a brief statement of the problem, a concise description of the research method and design, a summary of major findings, including their significance or lack of it, and conclusions.